Pranata Keluarga Muslim dalam Sistem Kekerabatan Parental Sunda - Iir Abdul Harits (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2008)
Basically dakwah deals with the problem of society living about institution and culture. It’s contalation in Sunda Societies become not simple. It’s dilemma to Da’i lies between holding strongly about legality of patriarkhis fiqh norms with Sunda culture system was developed and aplicated in society, because it is loss or elimited basic anthropologis.